A Computational Code for Sand Erosion Prediction in Elbows and Tees: An Improvement to the Direct Impingement Model to Account for Temperature Dependence - Mohyaldinn, Mysara Eissa (Australasian Corrosion Association ACA, 2010)
Prediction of erosion rate is important for material selection and operations design in production and transportation of oil and gas industry. Using Visual Basic Programming (VB6), a computational package was developed to provide a comprehensive sand erosion prediction tool. The two models used are the Salama Model and direct impingement model (DIM). In the Salama Model, the particle’s velocity is assumed to be the same as the fluid velocity while in the DIM model; the sand particle velocities are estimated and substituted in the erosion model. Both models are critically reviewed and verified using measured data. The developed package is used to investigate the effects of different parameters on erosion rate. The parameters investigated are flow velocity, pipe diameter, and sand production rate. The effect of temperature on fluid viscosity and hence erosion rate is also investigated.